Risk Evaluation Model in Food Supply Chain Using Integration grey-DEMATEL-ISM - Saragih, Hendrik Vicarlo; Vanany, Iwan (Journal of International Conference Proceedings, 2022)
The food supply chain has a complex structure because it is a perishable product and involves many stakeholders. Because of this complexity, the food supply chain will confront a few sorts of risks. This study means to create a risk assessment model in the food supply chain. Pareto analysis was used to identify risks based on the responses of 5 experts from companies and academics in the food sector. Then, the Decision-Making Trial and Evaluation Laboratory (DEMATEL) method based on grey system theory was utilized to evaluate the causal relationship between identified risks in the food supply chain. Furthermore, the grey-DEMATEL method was developed by combining it with the Interpretive Structural Modeling (ISM) method which can construct and visualize the relationship between risks into a graphic diagram. By integrating the three methods, three critical risks are found is lack of skilled labor, legal and regulatory, and communication failures. The results of this study can help companies to formulate risk mitigation strategies that have been identified in the food supply chain. This research can be expanded by verifying the data statistically using the system dynamics modeling (SDM) method or other statistical methods. Keywords: Decision-Making Trial and Evaluation Laboratory (DEMATEL), Food Risk, Grey system theory, Interpretive Structural Modeling (ISM), Supply Chain Risk